Functional abdominal pain. Issue 957 (5th July 2005) - Matthews, P J; Aziz, Q
Abstract : Functional abdominal pain or functional abdominal pain syndrome (FAPS) is an uncommon functional gut disorder characterised by chronic or recurrent abdominal pain attributed to the gut but poorly related to gut function. It is associated with abnormal illness behaviour and patients show psychological morbidity that is often minimised or denied in an attempt to discover an organic cause for symptoms. Thus the conventional biomedical approach to the management of such patients is unhelpful and a person's symptom experience is more usefully investigated using a biopsychosocial evaluation, which necessarily entails a multidisciplinary system of healthcare provision. Currently the pathophysiology of the disorder is poorly understood but is most likely to involve a dysfunction of central pain mechanisms either in terms of attentional bias, for example, hypervigilance or a failure of central pain modulation/inhibition. Although modern neurophysiological investigation of patients is promising and may provide important insights into the pathophysiology of FAPS, current clinical management relies on an effective physician-patient relationship in which limits on clinical investigation are set and achievable treatment goals tailored to the patient's needs are pursued.